Análise de estruturas marítimas e sistemas flexíveis constituídos por cabos - Mourelle, Márcio Martins (1984)
This work presents a procedure to nonlinear analysis of marine structures with cable arrays, by using the finite element method. A catenary cable element is employed. A computer program has been developed, using FORTRAN language and implemented in the system Burroughs B6700. This program allows statics analysis, free vibration, and dynamic analysis by modal superposition or direct integration method. Distributed loads acting on cable and framed structures from wave, current, self weight and buoyancy, can be evaluated automatically. Wave characteristics are calculated by the linear Airy Theory. A linear profile for current velocity is assumed. The induced loads are evaluated using Morison's equation. Simulation of real problems can be caried out by using nonlinear springs, spherical rigid bodies and prescribed displacements.